Symptoms and indicators of change in physical condition of students in 4-5 classes in the implementation of existing programs in physical education - Prozar Nikolaj Vladimirovich; Iedynak Gennadij Anatolievich (Kharkov National Pedagogical University, 2011)
The efficiency of the existing content of physical education to improve the physical condition of students 4-5 classes. In the experiment took part 110 students of the 4th class and 95 students of 5th one. Established lack of effectiveness of physical education content to improve the physical condition of students. Established that the physical preparedness of individual states to improve performance only. It is established that the expression and functional performance trends should be considered when determining the optimal parameters of physical activity of pupils. It is shown that the optimum parameters of four classes of physical activity contribute to the development of the muscular system.